"Building Nations through Shared Experiences: Evidence from African Football": a Replication of Depetris-Chauvin, Durante and Campante (2020) - Léonie Delpeyrou; Simone Bertoli (Institute for Replication (I4R), 2024)
Depetris-Chauvin et al. (2020) analyze the effects of football on civil conflict in Africa. We engage into a replication of their analysis. This unveils major inconsistencies between the sample selection criteria described in the article and the composition of the estimation sample (41 errors for 109 country qualification campaign pairs). Once these inconsistencies are removed, the evidence on the effect of a close qualification to the African Cup of Nations on conflict becomes substantially weaker. Several specifications produce a non-significant coefficient for the treatment. The placebo test proposed by the Authors themselves casts doubts on the validity of the identifying assumption in most specifications with a significant effect of the treatment.
Keywords: 330